Optimizing Biobriquette Quality : The Role of Raw Material Selection in Tapioka Based Binder System - Fatmayati Fatmayati; Anna Dhora; Romiyadi Romiyadi (Universitas Islam Raden Rahmat, Malang, 2025)
The continuous increase in energy consumption, along with the gradual depletion of fossil fuel reserves, highlights the need for sustainable alternative energy sources. Oil palm biomass waste is a promising raw material due to its abundance and high calorific value. This study aims to investigate the production process of biobriquettes made from four types of oil palm waste leaves, fronds, trunks, and shells using natural tapioca starch as a binder. The experimental procedure consisted of several stages: raw material preparation (cleaning, cutting into 1–3 cm pieces, and sun-drying), carbonization by incomplete combustion (pyrolysis) for approximately three hours, grinding and sieving through a 60-mesh screen, mixing the charcoal with 17% tapioca binder solution (starch-to-water ratio of 1:7), manual pressing, and oven drying at 105°C for ten hours. The resulting biobriquettes were evaluated based on SNI 01-6235-2000 standards, including moisture content, ash content, volatile matter, fixed carbon, and burning rate. The trunk-based biobriquette exhibited the best performance, with 5.10% moisture, 5.95% ash, 12.95% volatile matter, 76.00% fixed carbon, and a burning rate of 0.1256 g/min. Most parameters met the SNI requirements, except for slightly lower fixed carbon content. Therefore, oil palm trunk biomass is recommended as the most suitable raw material for producing high-quality, eco-friendly biobriquettes.